Who leads financial markets? - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
The present paper embarks on an analysis of interactions between the US and Euroland in the capital, foreign exchange, money and stock markets from 1994 until 2006. Considering influences on financial market volatility, the estimations are carried out in multivariate EGARCH models using structural residuals. This approach consequently allows identifying the contemporaneous effects between the daily variables. Structural VARs or VECMs can therefore give answers to the question of financial markets leadership: Generally speaking, the US effects on Europe still dominate, but the special econometric methodology is able to uncover otherwise neglected effects in the reverse direction.
Keywords: C32; G15; 330; Structural EGARCH; Financial Markets; United States; Euro Zone; Internationaler Finanzmarkt; Internationaler Preiszusammenhang; Volatilität; ARCH-Modell; EU-Staaten; USA